Observation Study on the Size Distribution of Sand Dust Aerosol Particles over Yinchuan, China - Jiandong Mao; Hongjiang Sheng; Hu Zhao; Chunyan Zhou (Advances in Meteorology)
The Yinchuan area, which lies in the eastern part of Northwest China, is one of the main transportation paths and origins of sand dust in China. In order to investigate the aerosol number size distribution and its temporal-spatial evolution over this area, direct solar radiation data taken from September 2012 to October 2013 by a sun photometer CE-318 located at Beifang University of Nationalities (106°29′E, 38°13′N) were analyzed. The particle number size distributions were retrieved from the aerosol optical depth (AOD) by use of the extinction inversion method. The experiment results show that although the averaged size distribution satisfies basically the Junge function, there are two obvious peaks at the particle radius of 0.6 μm and 1.4 μm, respectively. Because sand-dust weather occurs frequently, the particle size distribution in Spring is obviously larger than that in other seasons, which coincides with AOD variation tendency. Moreover, in sand-dust weather the particles number concentration is larger than that of background weather with one order of magnitude, especially for the number of concentration of large particles and giant particles. The research results have very important reference value for quantitative study of the influence of aerosol on atmosphere physics and chemistry process and monitoring of sand-dust weather and air pollution of this area.